Synthesis of radioactively labelled CdSe/CdS/ZnS quantum dots for in vivo experiments - Stachowski, Gordon M.; Bauer, Christoph; Waurisch, Christian; Bargheer, Denise; Nielsen, Peter; Heeren, Jörg; Hickey, Stephen G.; Eychmüller, Alexander (Beilstein Journal of Nanotechnology, 2014)
During the last decades of nanoparticles research, many nanomaterials have been developed for applications in the field of bio-labelling. For the visualization of transport processes in the body, organs and cells, luminescent quantum dots (QDs) make for highly useful diagnostic tools. However, intercellular routes, bio-distribution, metabolism during degradation or quantification of the excretion of nanoparticles, and the study of the biological response to the QDs themselves are areas which to date have not been fully investigated. In order to aid in addressing those issues, CdSe/CdS/ZnS QDs were radioactively labelled, which allows quantification of the QD concentration in the whole body or in ex vivo samples by γ-counting. However, the synthesis of radioactively labelled QDs is not trivial since the coating process must be completely adapted, and material availability, security and avoidance of radioactive waste must be considered. In this contribution, the coating of CdSe/CdS QDs with a radioactive 65ZnS shell using a modified, operator-safe, SILAR procedure is presented. Under UV illumination, no difference in the photoluminescence of the radioactive and non-radioactive CdSe/CdS/ZnS colloidal solutions was observed. Furthermore, a down-scaled synthesis for the production of very small batches of 5 nmol QDs without loss in the fluorescence quality was developed. Subsequently, the radio-labelled QDs were phase transferred by encapsulation into an amphiphilic polymer. γ-counting of the radioactivity provided confirmation of the successful labelling and phase transfer of the QDs.
Keywords: biomarker; CdSe/CdS/ZnS; quantum dots; radioactive labelling; 65Zn